Halku’l-Kur’an tartışmalarının siyasi, sosyal ve itikadi boyutları: (Me’mun dönemi örneği) - Yıldız, Mahmut (My University, 2003)
THE POLITICAL, SOCIAL AND RELIGIOUS DIMENSIONS OF THE DISCUSSIONS OF CREATEDNESS OF QURAN (THE EXAMPLE OF THE PERIOD OF MA'MUN) The problem of createdness of Quran had not been discussed in the time of Prophet Mohammad and Sahaba because it was not a problem related with the essence of the Islamic belief. However, it is a philosophical and religious problem coming out because of the conflicts among Muslims and of the process of interaction with other cultures and believes as a result of the expansion of border of the Islamic state. The thought of createdness of Quran defended by non-Arabs (Mawali) had not been supported, adverse, had been firmly hindered in the period of Amawites and early Abbasites. However, in the time of Caliph al-Ma'mûn, scholars of Mu'tazila had made him to adopt the doctrine of createdness of Quran and the doctrine had become the official ideology of state. During the process, called as Mihna, the thoughts of Mu'tazila had been firmly enforced and the scholars opposing the doctrine had been prosecuted by government. The Mihna had continued in the times of Caliph al-Mu'tasım and of Caliph al-Wasık until the time of Caliph al-Mutawakkil on the reign of whom the discussions concerning the doctrine of createdness of Quran had been forbidden and Mu'tazilities had been replaced with scholars of Hadith and Fıqh. Mahmut YILDIZ

HALKU'L-KUR'ÂN TARTIŞMALARININ SİYASÎ, SOSYAL VE İTİKÂDÎ BOYUTLARI ( ME'MÛN DÖNEMİ ÖRNEĞİ ) Halku'l-Kur'ân meselesi İslâm inanç esaslarından biri olmadığı için, Hz. Muhammed (s.a.v.) ve Sahâbe döneminde tartışılmamıştır. Bununla birlikte, müslümanlar arasındaki iç çatışmalar ve İslâm Devleti sınırlarının genişlemesinin sebep olduğu diğer kültür ve inançlarla etkileşim sürecinde ortaya çıkan felsefî ve dinî bir problemdir. Arap olmayanlar (Mevâlî) tarafından savunulmuş olan Halku'l-Kur'ân düşüncesi, Emevîler ve ilk dönem Abbâsî yönetimi tarafından destek görmemiş, aksine, sert bir şekilde engellenmiştir. Ancak, Halife Me'mûn döneminde Mu'tezilî âlimler Halku'l-Kur'ân düşüncesini halifeye kabul ettirerek, onu devletin resmî ideolojisi haline getirdiler. Mihne olarak adlandırılan bu süreçte, Mu'tezile'nin fikirleri sert bir şekilde kabul ettirilmeye çalışıldı ve Halku'l-Kur'ân düşüncesine muhalif olan âlimler yönetim tarafından kovuşturmaya uğradı. Mihne, Halife Mu'tasım ve Vâsık dönemlerinde de devam etti. Fakat, Halife Mütevekkil döneminde Halku'l-Kur'ân tartışmaları yasaklandı ve Mu'tezilî âlimlerin yerini hadis ve fıkıh âlimleri aldı. Mahmut YILDIZ
Keywords: Din; İslam ahlâk ve adâbı; İslam Dini; İslam Mezhepleri; Kur’an-ı Kerim